Heritage and the making of political legitimacy in Laos : the past and present of the Lao nation - Wilcox, Phill (Asian heritages (Amsterdam, Netherlands), 2021)
The Lao People's Democratic Republic is nearly fifty years old, and one of the few surviving one-party socialist states. Nearly five decades on from its revolutionary birth, the Lao population continues to build futures in and around a political landscape that maintains socialist rhetoric on the one hand and capitalist economics on the other. Contemporary Lao politics is marked by the use of cultural heritage as a source of political legitimacy. Researched through long-term detailed ethnography in the former royal capital of Luang Prabang, itself a UNESCO-recognized World Heritage Site since 1995, this book takes a fresh look at issues of legitimacy, heritage, and national identity for different members of the Lao population. It argues that the political system has become sufficiently embedded to avoid imminent risk of collapse but suggests that it is facing new challenges primarily in the form of rising Chinese influence in Laos.